PERBEDAAN KEKUATAN TARIK ANTARA FIBER REINFORCED COMPOSITE DENGAN FIBER SISAL (Agave sisalana) TERALKALISASI DAN NON-ALKALISASI - , FEMI ZULHIMA HANIFA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fiber reinforced composite (FRC) is a material that contains a matrix as the main ingredient and is reinforced with fibers. FRC application in the oral cavity as a framework fixed denture requires considerable tensile strength to withstand the mastication force. One of the factors that can increase the tensile strength is alkalization. This study was to determine the differences in the tensile strength between FRC with alkalized sisal fiber (Agave sisalana) and the non-alkalized one. This research material was FRC with flowable composite matrix (Master Flow, Brazil) and sisal fiber (Agave sisalana) (Balittas, Indonesia). The size of the sample mold was based on ASTM D638-02a that is 10x3x2mm with the test area of 32x10x2mm. This study used 8 samples which were then divided into 2 treatment groups (n=4). The first was the alkalization carried out by soaking the fiber in 5% NaOH solution for 4 hours which was then dried in an oven for 24 hours at 80° C and the second was the non-alkalized fiber as a control group. Samples were irradiated using a light curing unit for 20 seconds and then soaked in distilled water for 24 hours at 37º C. The tensile strength was measured using the universal testing machine at a speed of 1mm/min. Tensile strength data were analyzed statistically using independent t-test. The results showed that the average tensile strength of FRC with the alkalized sisal fiber (Agave sisalana) was 46.97 ± 4.40 MPa and that with nonalkalization was 28.40 ± 5.33 MPa. The independent t-test indicated that there was a significant difference in tensile strength between the alkalized and the nonalkalized fiber (p <0.05). This study reveals that the tensile strength of FRC with the alkalized sisal fiber (Agave sisalana) was higher than that of the non-alkalized sisal fiber (Agave sisalana). Key word: FRC, sisal fiber, alkalization, tensile strength